THE EFFECT OF SCIENCE INQUIRY LEARNING MODEL WITH PICTORIAL RIDDLE METHOD ON STUDENTS SCIENCE PROCESS SKILLS IN ELASTICITY TOPIC SENIOR HIGH SCHOOL PERCUT SEI TUAN CLASS XI ACADEMIC YEAR 2018/2019 - Yuni Evany Sinaga; Nurdin Siregar; Disna Margaretha (UNIVERSITAS NEGERI MEDAN, 2019)
This study aimed to determine the effect of scientific inquiry learning with pictorial riddle method on students' science process skills in the subject elasticity in senior high school Percut Sei Tuan. This research was a quasi-experiment with two group pre-test post-test design. The population in this study were all students of class XI MIA SMA N 2 Percut Sei Tuan consisting of 4 classes totalling 140 students. The study sample consisted of two classes, namely the XI MIA-1 class as the experimental class and the XI MIA-2 class as the control class with 35 and 34 students, respectively. The instrument used was an essay test of science process skills. Based on the data analysis, it was found that there was a significant effect of the scientific inquiry learning with the pictorial piddle method on students' science process skills in the subject elasticity in Senior High School 2 Percut Sei Tuan.Keywords: science process skills, scientific inquiry, elasticity